In vitro complement activation, adherence to red blood cells and induction of mononuclear cell cytokine production by four strains of Aggregatibacter actinomycetemcomitans with different fimbriation and expression of leukotoxin. (24th September 2016) - Damgaard, C.; Reinholdt, J.; Palarasah, Y.; Enevold, C.; Nielsen, C.; Brimnes, M. K.; Holmstrup, P.; Nielsen, C. H.
Abstract : Background and Objective: The periodontal pathogen Aggregatibacter actinomycetemcomitans has been proposed as pro‐atherogenic, and complement‐mediated adherence to red blood cells (RBCs) may facilitate its systemic spread. We investigated the ability of four strains of A. actinomycetemcomitans with differential expression of leukotoxin A (LtxA) and fimbriae to activate complement, adhere to RBCs and elicit cytokine responses by mononuclear cells (MNCs). Material and Methods: Aggregatibacter actinomycetemcomitans serotype b strains HK 921, HK 1651, HK 2092 and HK 2108 were fluorescence‐labeled, incubated with human whole blood cells in the presence of autologous serum, and assessed for RBC adherence by flow cytometry and for capacity to induce cytokine production by cytometric bead array analysis. The levels of IgG to A. actinomycetemcomitans serotype b were quantified by ELISA, as was consumption of complement. Results: The JP2 clone variants HK 1651 and, to a lesser extent, HK 2092, consumed complement efficiently, while HK 2108 (= strain Y4) consumed complement poorly. Nonetheless, the four tested strains adhered equally well to RBCs in the presence of autologous serum, without causing RBC lysis. The JP2 clone variant HK 2092, selectively lacking LtxA production, induced higher production of tumor necrosis factor (TNF)‐α, interleukin (IL)‐1β, IL‐6 and IL‐10 by MNCs than did the other three strains, while the four strains induced similar production of IL‐12p70. RBCs facilitated the HK 2092‐induced production of TNF‐α and IL‐1β, and IL‐6 was enhanced by RBCs, and this facilitation could be counteracted by blockade of complement receptor 3 (CD11b/CD18). Conclusion: Our data suggest that the JP2 clone of A. actinomycetemcomitans, most closely resembled by the variant HK 1651, activates complement well, while strain Y4, represented by HK 2108, activates complement poorly. However, all strains of A. actinomycetemcomitans adhere to RBCs and, when capable of producing LtxA, prevent production of inflammatory cytokines by MNCs. This "immunologically silent" immune adherence may facilitate systemic spread and atherogenesis.